Generation of heat maps for the preservation of biological diversity up to mine closure by computer programming - Julca, D; Espinoza, J (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
Mine Closure is a legal instrument that guarantees the prevention, minimization, control of risks and effects on health, safety of people, environment, surroundings, property that could be generated during the completion of mining operations. The description of the biological environment is part of the content of the Mine Closure Plan and includes the characterization and dynamics of the flora and fauna, based on biological diversity indexes such as abundance, distribution, conservation status, according to the national list of endangered species and degree of endemism. Additionally, the characterization of fragile ecosystems, Natural Areas, Buffer Zones, landscape units and elements that could threaten the conservation of ecosystems. It is of utmost importance to integrate biological information due to the intrinsic value of biological diversity, ecological, genetic, social, economic, scientific, educational, cultural, recreational and aesthetic values of biological diversity. These indices measure the impact before, during and after the cessation of mining operations, numerically; however, this data does not allow us to visually observe the impact on flora and fauna communities. Therefore, there is a need to generate tools that optimize the evaluation of the impact on the biological environment and thus generate strategies that allow its conservation. The objective of this project is the development of computer tools that allow visualizing the impact that mining activities have had on the flora and fauna communities, from the construction phase to the moment of its closure. Programming in Python language in conjunction with ArcGIS software makes it possible to generate "heat maps" in an instantaneous, versatile and adaptable way for the analysis of flora and fauna communities. Through the tool, the user will be able to enter information and maintain an updated database, obtained from biological monitoring of flora or fauna, generating visual representations and values. In order to analyze any disturbance in the species and their ecosystems, with the purpose of implementing timely strategies to minimize their affectation and guarantee the conservation of the species to the communities or parts of interest.